Analysis Community Competence Development in Improving Live through Small and Medium Enterprise Investment in the Pandemic Era in East Timor - Julio Lino Tilman (Research Synergy Foundation, 2021)
Community competence development in improving life through investing in small and medium enterprises is one of the beneficial alternatives for groups and individuals for the welfare of the superior local community's wellbeing. The purpose of this study is to determine the basic provisions of the small and medium business investment group in the local area, related to hard and soft competence, which are used as criteria for giving, receiving, and solving problems. The method used in this study used a thematic descriptive qualitative analysis approach; the sampling method was taken by six people representing 28 people, including the core structure for semi-structured interviews. The technique used is a non-probability sample by exploring sources of information using purposive sampling and snowball sampling. From the results, it was found that the educational background was sufficient and still had shortcomings in hard and soft competencies, including creativity and technical skills. So, there are several suggestions, namely (1) to take additional training on creativity and technical skills to increase in-depth understanding, (2) for other studies that are interested in deepening research in that location. In terms of investment development, it can compete in national and international markets. These results also provide input for the investment group to learn hard and soft competencies and specifically creative abilities and technical skills to find learning resources that ensure development is related to investment in the digital era.